Rural tourism in backward areas: evidences from the portuguese municipality of Almeida - Fonseca, Fernando Pereira da (2009)
Rural tourism (RT) has been widely seen in the last years as an effective way of addressing the socioeconomic problems of inner areas where primary traditional activities are in decline. The growth verified both in supply and demand highlight the importance of the rural tourism phenomena. Nevertheless, the RT impact is controversial and not always evident. In this context, this paper presents the main conclusions of a research undertaken in the Portuguese peripheral and rural municipality of Almeida, where tourism is claimed as the most promising activity to surpass the current trend of decline. Data were collected from municipal RT entrepreneurs using a previously applied survey about perceptions and attitudes of tourism development in the municipality. The findings suggest that the contribution of RT in the socioeconomic regeneration and in the heritage rehabilitation is limited, contradicting some generalized rhetoric and policies. The main weaknesses are related with the low demand, the lack of essential skills, the reduced returns obtained and the lack of local cooperation. Due to the common nature of problems involved, some conclusions of this research can be extrapolated to other Portuguese peripheral and rural territories.